Analysis of Mathematics Learning Management in Improving Student Achievement at Al Azhar Medan Superior High School - Nurhayati Nurhayati; Risna Mira Bella Saragih; Khoiruddin Matondang; Siswadi Siswadi (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to describe the management of mathematics learning in improving student achievement at Al Azhar Superior High School Medan. This study uses a qualitative approach with a descriptive type of research. The research subjects consisted of mathematics teachers, vice principals for curriculum, and students selected through purposive sampling techniques. Data was collected through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawn. The validity of the data is carried out through triangulation of sources, techniques, and time. The results of the study show that mathematics learning management has been carried out well through systematic planning, implementation, and evaluation of learning. In the planning stage, teachers prepare teaching modules, learning objectives, strategies, media, and evaluation instruments. In the implementation stage, teachers apply varied learning methods, conducive classroom management, and the use of digital media to increase student activity. At the evaluation stage, teachers conduct assessments, provide feedback, and remedial for students. Supporting factors include school facilities, teacher competence, and school support, while barriers include differences in students' abilities and limited learning time. Good learning management contributes to increasing students' motivation, activeness, and mathematics learning achievement.